The Role of Trust as a Mediator Between System Characteristics and Response Behaviors. (September 2015) - Chancey, Eric T.; Bliss, James P.; Proaps, Alexandra B.; Madhavan, Poornima
Objective: The purpose of the current work was to clarify how subjective trust determines response behavior when interacting with a signaling system. Background: In multiple theoretical frameworks, trust is acknowledged as a prime mediator between system error characteristics and automation dependence. Some researchers have operationally defined trust as the behavior exhibited. Other researchers have suggested that although trust may guide operator responses, trust does not completely determine the behavior. Method: Forty-four participants interacted with a primary flight simulation task and a secondary signaling system task. The signaling system varied in reliability (90%, 60%) and error bias (false alarm, miss prone). Trust was measured halfway through the experimental session to address the criterion of temporal precedence in determining the effect of trust on behavior. Results: Analyses indicated that trust partially mediated the relationship between reliability and agreement rate. Trust did not mediate the relationship between reliability and reaction time. Trust also did not mediate the relationships between error bias and reaction time or agreement rate. Analyses of variance generally supported specific behavioral and trust hypotheses, indicating that the paradigm employed produced similar effects on response behaviors and subjective estimates of trust observed in other studies. Conclusion: These results indicate that strong assumptions of trust acting as the prime mediator between system error characteristics and response behaviors should be viewed with caution. Application: Practitioners should consider assessing factors other than trust to determine potential operator response behaviors, which may be more predictive.